Urban open spaces as commons: The case of the self-governed Navarinou park - Arvanitidis, Paschalis A.; Papagiannitsis, George (The Greek Review of Social Research, 2020)
Creating commons in vacant, open, urban spaces constitutes an innovative solution for the sustainable management of these places and the mitigation of the environmental, economic and social burdens that urban dwellers face. The paper uses the self-governed Navarinou park as a case study, in order to discuss the issue, evaluate its experience and propose possible policies for successful such actions. In particular, it employs the SES methodological framework of the Ostromian approach to outline the Park as a commons institution and to explore its variables. It concludes that the Park constitutes a functional and credible institution, and as such an advisable intervention would be the recognition of collective rights and practices alongside the development of a framework that would allow such endeavors to thrive.